Ensino de Ciências nos anos iniciais do ensino fundamental: o que dizem os professores - Oliveira, Ana Paula Fantinati Menegon de [UNESP] (2015)
The research aimed to identify and analyze through reports, the views of a group of teachers who have endured or are acting in the early years of Elementary School, on: the development, the challenges and difficulties in Science Teaching this stage of schooling. This work has guided a qualitative approach, in which data were collected through a questionnaire with open and closed questions, sent via electronic mail to graduates in Pedagogy Degree course in the period 2005-2012 of a University Public State. Effectively participated 27 educators. We used the content analysis proposed by Bardin (1977) to systematize the information obtained. The data indicate that there is clarity about the importance of science education for all respondents, believing it to be possible to work with scientific content with students in the early years of Elementary School. This position is justified on the grounds that the Sciences enable students to understand and know better themselves and the world. Quote from the contents that should be worked: the environment/living beings and human and health. They mention that the best way to teach science to children is through contextualization strategy and use of activities and concrete materials and experimentation. In the classroom, they present a Science Teaching based on the use of research/research and contextualization, citing the use of activities, materials and textbooks. The main sources of teachers' studies are the internt and books. they are professional who, for the most part, they feel prepared to teach science by studying/pesquisarem/seek content, solving doubts or difficulties. The biggest challlenges, they say, to science education for children is teaching and learning in order to achieve effectively enable students to take ownership of the worked-content. The greatest difficulty for them is under the conditions of the schools, followed by teacher training. Points out the need of initial training...